Implementing Podcast with Transcript Through Reading-While-Listening Strategy to Improve Students’ Listening Comprehension - Maulidea Putri Artikasari; Mirjam Anugerahwati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
This classroom action research aimed at improving EFL students’ listening comprehension using the implementation of podcast with transcripts through reading-while-listening strategy. The result of mean score in final test showed 81. 95 which increased 13. 05 points from initial test and discovered that 86 % of students achieved the standard passing score. Likewise, the second semester students revealed that they get used to being actively involved in the discussion and showed their enthusiasm during the teaching and learning process. In conclusion, reading-while-listening strategy serves as an effective teaching strategy especially for low-level students to improve their comprehension in listening skills.